Effectiveness of COVID-19 Vaccines in Patients Under Maintenance Hemodialysis - Mahallawi WH; Ibrahim NA; Mumena WA (Dove Medical Press, 2021)
Waleed H Mahallawi,1 Nadir A Ibrahim,1 Walaa A Mumena2 1Medical Laboratory Technology Department, College of Applied Medical Sciences, Taibah University, Madinah, Saudi Arabia; 2Department of Clinical Nutrition, College of Applied Medical Sciences, Taibah University, Madinah, Saudi ArabiaCorrespondence: Waleed H MahallawiMedical Laboratory Technology Department, College of Applied Medical Sciences, Taibah University, Madinah, Saudi ArabiaEmail wmahallawi@taibahu.edu.saBackground: Several published data on the dialysis population showed that antibody levels decreased after COVID-19 vaccinations in comparison to the overall population. We aimed to illustrate the persistence of humoral response after receiving second dose of the Pfizer or AstraZeneca vaccines in patients under maintenance hemodialysis (HD).Methods: A total of 119 adult patients on HD who were recruited from a single hemodialysis center in Madinah, Saudi Arabia. An enzyme-linked immunosorbent assay (ELISA) was utilized to measure the specific antibody response to the spike protein in the serum samples.Results: Mean age of patients was 48.5 ± 13.5 years, while mean time since starting the renal dialysis was 5.09 ± 5.29 years. Blood samples were collected after 89.2 ± 25.7 days of receiving the second dose of the vaccines. A very high positive correlation between anti-S IgG antibodies in pre- and post-dialysis was found (rs= 0.93, p < 0.001). Additionally, there was a high positive correlation between anti-S IgG antibody collected at baseline and follow-up blood samples (30 days apart) (rs= 0.82, p < 0.001). Moreover, patients who received Pfizer had significantly higher mean change in anti-S IgG antibodies compared to patients who received AstraZeneca (0.41 ± 0.94 vs 0.03 ± 0.30, respectively, p = 0.026).Conclusion: The majority of the patients included in this study were able to yield an immune response to the vaccine after receiving the two doses. Persistence of IgG antibodies in the majority of the patients on HD in response to COVID-19 vaccines is encouraging in terms of continuing to vaccinate this category of patients in addition to monitoring them.Keywords: SARS-CoV-2, maintenance hemodialysis, COVID-19 vaccines, chronic kidney disease